1988
DOI: 10.1002/ajpa.1330770116
|View full text |Cite
|
Sign up to set email alerts
|

New method for assessing changes in growth and sexual dimorphism in paleoepidemiology

Abstract: This paper has three goals. First, traditional methods used for analyzing growth disruption (GD) and sexual dimorphism (SD) in prehistoric skeletal populations are critiqued. Second, a new method, using adult vertebrae, is presented which helps overcome these limitations. Third, this new method is then tested in the Dickson Mounds skeletal population. Between A.D. 950 and 1300 this population underwent a transition from hunting and gathering (PreMississippian: PreMiss.) to maize horticulture (Mississippian: Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…This does not affect the nature of the results as Clark and colleagues found that T10 and T11 were amongst the vertebrae whose neural canal growth was stunted by environmental stress. It has been postulated that the AP and TR diameters of the neural canals represent separate growth periods (Clark, 1988). This suggests that the individuals of Fishergate House did not experience environmental stress that was severe enough to disrupt growth during critical periods of AP neural canal development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This does not affect the nature of the results as Clark and colleagues found that T10 and T11 were amongst the vertebrae whose neural canal growth was stunted by environmental stress. It has been postulated that the AP and TR diameters of the neural canals represent separate growth periods (Clark, 1988). This suggests that the individuals of Fishergate House did not experience environmental stress that was severe enough to disrupt growth during critical periods of AP neural canal development.…”
Section: Discussionmentioning
confidence: 99%
“…Small VNC size is a non‐specific indicator of stress as it has multiple, non‐specific aetiologies involving malnutrition and periods of infection (Clark et al ., 1985). Whereas catch‐up growth in height can sometimes hide the effects of early developmental stress, the anterio‐posterior (AP) and transverse (TR) diameters (Figure 1; Clark et al ., 1985; Clark, 1988) of the neural canals will remain small as these elements undergo much of their growth in early childhood. At birth they have achieved 65% of their full adult size and by four years of age they are around 80% complete (Hinck et al ., 1966).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of the anteroposterior (AP) and transverse diameters (TR) of the neural canal is predominantly complete in early childhood, reaching ∼95% of its final size by 5 years of age (Diméglio, 1993). Consequently, evidence of growth disturbance during early postnatal life may become “locked into” these dimensions (Clark et al, 1986; Clark, 1988; Diméglio, 1993; Larsen, 1997; Watts, 2011, 2013a,b). The value of the AP and TR dimensions of the vertebrae has been previously recognized and implemented in both adult (Clark et al, 1986; Clark, 1988; Watts, 2011, 2013a,b) and non‐adult (Watts, 2013b) skeletal collections.…”
Section: The Process Of Vertebral Growthmentioning
confidence: 99%
“…Consequently, evidence of growth disturbance during early postnatal life may become “locked into” these dimensions (Clark et al, 1986; Clark, 1988; Diméglio, 1993; Larsen, 1997; Watts, 2011, 2013a,b). The value of the AP and TR dimensions of the vertebrae has been previously recognized and implemented in both adult (Clark et al, 1986; Clark, 1988; Watts, 2011, 2013a,b) and non‐adult (Watts, 2013b) skeletal collections. However, these measurements, as well as that of vertebral body height, have yet to be explored as a potential method to map the growth of non‐adults.…”
Section: The Process Of Vertebral Growthmentioning
confidence: 99%